Pregunta
upstudy study bank question image url

Determine the value of the expression without the use of a culculator: \[ \frac{\tan 300^{\circ}+\cos \left(90^{\circ}+x\right)}{\sin \left(180^{\circ}-x\right)+2 \cos \left(-30^{\circ}\right)} \] Prove the following identity: \( \frac{1-\sin 2 x}{\cos 2 x}=\frac{\cos x-\sin x}{\cos x+\sin x} \) Determine the general solution of \( \cos x-\sin x=\sqrt{2} \)

Ask by Harris West. in South Africa
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The expression evaluates to –1. The identity is proven as shown. The general solution of the equation is x = 2πk − π⁄4 for any integer k.

Solución

We will solve three parts: ────────────────────────────── Part 1. Evaluate   A = [tan 300° + cos(90° + x)] ⁄ [sin(180° − x) + 2 cos(−30°)] Step 1. Compute tan 300°.  • Note that 300° = 360° − 60°, so   tan 300° = tan(−60°) = −tan 60° = −√3. Step 2. Compute cos(90° + x).  • Using the identity cos(90° + x) = −sin x, we get   cos(90° + x) = −sin x. Step 3. Compute sin(180° − x).  • Recall sin(180° − x) = sin x. Step 4. Compute cos(−30°).  • Since cosine is even, cos(−30°) = cos 30° = √3⁄2. Step 5. Write the numerator and denominator.  • Numerator: tan 300° + cos(90° + x) = (−√3) + (− sin x) = − (√3 + sin x).  • Denominator: sin(180° − x) + 2 cos(−30°)         = sin x + 2(√3⁄2) = sin x + √3. Step 6. Divide the two:   A = [−(√3 + sin x)] / (sin x + √3) = −1. Thus, the value of the expression is –1. ────────────────────────────── Part 2. Prove the identity   (1 − sin 2x)⁄(cos 2x) = (cos x − sin x)⁄(cos x + sin x) Proof: Step 1. Express sin 2x and cos 2x in terms of sin x and cos x.  • sin 2x = 2 sin x cos x,  • cos 2x = cos²x − sin²x. Step 2. Substitute into the left-hand side (LHS):   LHS = (1 − 2 sin x cos x)⁄(cos²x − sin²x). Step 3. Notice that the numerator can be written as:   1 − 2 sin x cos x = (sin²x + cos²x) − 2 sin x cos x = cos²x − 2 sin x cos x + sin²x = (cos x − sin x)². Step 4. Also, write the denominator as:   cos²x − sin²x = (cos x + sin x)(cos x − sin x). Step 5. Substitute these into LHS:   LHS = [(cos x − sin x)²]⁄[(cos x + sin x)(cos x − sin x)]. Provided cos x − sin x ≠ 0 (which is acceptable for the identity’s validity), one factor cancels:   LHS = (cos x − sin x)⁄(cos x + sin x). This is exactly the right-hand side (RHS). Hence, the identity is proven. ────────────────────────────── Part 3. Determine the general solution of   cos x − sin x = √2 Solution: Step 1. Recognize that the left side can be written in the form R cos(x + φ). In fact, note that   cos x − sin x = √2 cos(x + π⁄4) Why?  • Recall cos(x + π⁄4) = cos x cos(π⁄4) − sin x sin(π⁄4)  • And since cos(π⁄4) = sin(π⁄4) = √2⁄2, we have   cos(x + π⁄4) = (√2⁄2)(cos x − sin x).  • Multiply both sides by √2:   √2 cos(x + π⁄4) = cos x − sin x. Step 2. Substitute into the equation:   √2 cos(x + π⁄4) = √2. Step 3. Divide both sides by √2 (assuming √2 ≠ 0):   cos(x + π⁄4) = 1. Step 4. Solve cosθ = 1.   We have cosθ = 1 when θ = 2πk for any integer k. Here θ = x + π⁄4, so:   x + π⁄4 = 2πk  ⇒  x = 2πk − π⁄4. Thus, the general solution is:   x = 2πk − π⁄4,  where k is any integer. ────────────────────────────── Summary of Answers: 1. The expression evaluates to –1. 2. The identity (1 − sin 2x)/(cos 2x) = (cos x − sin x)/(cos x + sin x) is proven as shown above. 3. The general solution of cos x − sin x = √2 is x = 2πk − π⁄4 for any integer k.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To tackle the expression first, we start with evaluating each trigonometric function involved. 1. **Evaluating the Expression** \(\tan 300^{\circ} = \tan(360^{\circ} - 60^{\circ}) = -\tan 60^{\circ} = -\sqrt{3}\). Next, \(\cos(90^{\circ} + x) = -\sin x\). For \(\sin(180^{\circ} - x) = \sin x\) and \(2 \cos(-30^{\circ}) = 2 \cdot \frac{\sqrt{3}}{2} = \sqrt{3}\). Putting it all together, the expression becomes: \(\frac{-\sqrt{3} - \sin x}{\sin x + \sqrt{3}}\). 2. **Proving the Identity** Starting with the left-hand side: \(\frac{1 - \sin 2x}{\cos 2x} = \frac{1 - 2 \sin x \cos x}{\cos^2 x - \sin^2 x}\). Rewrite \(1\) in terms of sines and cosines: \(\frac{\cos^2 x + \sin^2 x - 2\sin x \cos x}{\cos^2 x - \sin^2 x} = \frac{(\cos x - \sin x)^2}{\cos^2 x - \sin^2 x}\). The right-hand side simplifies to: \(\frac{(\cos x - \sin x)(\cos x - \sin x)}{(\cos x - \sin x)(\cos x + \sin x)}\), thus confirming the equality. 3. **Finding the General Solution** To solve \(\cos x - \sin x = \sqrt{2}\), we rewrite it as: \(\sqrt{2} = \sqrt{\cos^2 x + \sin^2 x} \cdot \left(\frac{\cos x}{\sqrt{2}} - \frac{\sin x}{\sqrt{2}}\right)\). The maximum deviation for \(\cos x - \sin x\) is \(\sqrt{2}\) when the angle \((\frac{\pi}{4} + n\pi)\) is adjusted to attain its max. Thus, valid solutions occur at \(\cos x - \sin x \leq 1\), leading to no solutions since \(\sqrt{2}\) exceeds the maximum reached by \(1\) on the interval. In conclustion, the expressions align with trigonometric identities, confirming no valid solutions exist for the given cosine-sine equation.

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad